The effects of organic matter and anaerobic oxidation of methane on the microbial sulfate reduction in cold seeps - Sun, Tiantian; Wu, Daidai; Wu, Nengyou; Yin, Ping (Frontiers in Marine Science, 2023)
Cold seep sediments are dominated by intensive microbial sulfate reduction coupled to anaerobic oxidation of methane. However, the contribution proportion between this process and the role of organic matter has remained enigmatic. Here, pore water data combined with PROFILE model, fluxes of sulfate and methane concentration calculated from Fick's first law, and δ34SSO4 and δ18OSO4 of pore water sulfate were studied to reconstruct co-occurring microbial organoclastic sulfate reduction and anaerobic oxidation of methane coupled with sulfate reduction in methane seep sediments collected from South China Sea. The sulfate concentration profiles of C9 and C14 in Qiongdongnan Basin generally show quasilinear depletion with depth. Reaction-transport modeling provided close fits to concentration data. δ18OSO4 and δ34SSO4 increase fastest with sediment depth above 400 cmbsf and slowest below that depth. The values of methane flux are always lower than those of total sulfate reduction of sulfate diffusive flux at GC-10, GC-9, GC-11 and HD319 sites in Taixinan Basin. Besides, positions of sulfate methane transition zone in all study sites are approximately 400 to 800 centimeters below seafloor. These results showed that microbial sulfate reduction in sediments is mainly controlled by intense anaerobic oxidation of methane, but there is a certain relationship with organic matter metabolism process. This emphasizes that traditional redox order of bacterial respiration is highly simplified, where, in sediments such as these seeps, all of these microbial sulfate reduction processes can occur together with complex couplings between them.